2007
DOI: 10.1103/physrevb.75.085202
|View full text |Cite
|
Sign up to set email alerts
|

Pauli blockade of the electron spin flip in bulk GaAs

Abstract: By means of time-resolved optical orientation under strong optical pumping, the k-dependence of the electron spin-flip time (τ sf ) in undoped GaAs is experimentally determined. τ sf monotonically decreases by more than one order of magnitude when the electron kinetic energy varies from 2 to 30 meV. At the high excitation densities and low temperatures of the reported experiments the main spin-flip mechanism of the conduction band electrons is the Bir-Aronov-Pikus. By means of Monte-Carlo simulations we eviden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The spin-flip is only allowed around the chemical potential, which suppresses the Bir-Aronov-Pikus spin relaxation at low temperature. Amo et al found similar arguments and results [392].…”
Section: Bir-aronov-pikus Mechanismsupporting
confidence: 67%
See 1 more Smart Citation
“…The spin-flip is only allowed around the chemical potential, which suppresses the Bir-Aronov-Pikus spin relaxation at low temperature. Amo et al found similar arguments and results [392].…”
Section: Bir-aronov-pikus Mechanismsupporting
confidence: 67%
“…Hence, the relevant spin relaxation mechanisms are the Bir-Aronov-Pikus and the D'yakonov-Perel' mechanisms. There has been a debate about the relative importance of these two mechanisms in intrinsic III-V and II-VI semiconductors [21,390,392,[584][585][586]. Single-particle theory based on the elastic scattering approximation comes to the conclusion that spin relaxation due to the Bir-Aronov-Pikus mechanism can be more important at low temperature and high hole density [390].…”
Section: Electron Spin Relaxation In Intrinsic Bulk Iii-v and Ii-vi Smentioning
confidence: 98%
“…This is comparable to values given in previous works published on undoped GaN [2,3]. If we analyze in detail the extracted time constants: with regard to the electrons, a time of 15 ps is, at least, an order of magnitude lower than what is measured, for example, on GaAs [7][8][9][10][11][12]. Concerning the holes, the relaxation of their pseudo-spin in semiconductors is influenced by the admixture of the valence subbands.…”
Section: Contributed Articlesupporting
confidence: 82%
“…28 In bulk system, similar problem also exists. 67 However, the KSBE approach keeps all the electron-hole exchange scattering terms, and thus gives correct results.…”
Section: Ksbesmentioning
confidence: 99%